Foundation Anchoring in Thawed Ground - Porkhaev,G. V. (1967)
The subject of anchoring foundations to withstand frost heave forces is of considerable interest. The paper gives a brief straightforward analysis of a case where the foundation is placed in unfrozen ground and is subjected to seasonal frost heave. Trans. of Akademiya Nauk SSSR. Institut Merzlotovedeniya. Trudy, v14 p56-59 1958, by G. K. Swinzow.